Regular Target Recognition Based on FAST Feature Point Extraction and Contour Recognition - Kang, Jinchuan; Lu, Jun; Zhang, Xu; Cao, Yuan (International Journal of Computer Science and Information Technology, 2024)
The research of regular target recognition based on FAST feature point extraction and contour recognition aims to develop an efficient target recognition method. In this method, the key feature points are extracted from images by FAST (Features from Accelerated Segment Test) algorithm, and then the target is identified and located by contour recognition technology. By combining these two technologies, the accurate detection and positioning of the target are realized, and the accuracy and efficiency of the target recognition are improved. In the experiment, this method shows good performance, high recognition accuracy and robustness. This research result provides a new idea and method for the further development of the field of object recognition, and has important theoretical and application value.